Valacyclovir Neurotoxicity and Nephrotoxicity in an Elderly Patient Complicated by Hyponatremia. (22nd June 2018) - Murakami, Takuya; Akimoto, Tetsu; Okada, Mari; Hishida, Erika; Sugase, Taro; Miki, Atsushi; Kohara, Marina; Yoshizawa, Hiromichi; Masuda, Takahiro; Kobayashi, Takahisa; Saito, Osamu; Muto, Shigeaki; et al.
A 66-year-old women with no history of renal disease was admitted due to a coma and acute kidney injury with a serum creatinine level of 7.44 mg/dL which were ascribed to valacyclovir neurotoxicity and nephrotoxicity, respectively. She had received valacyclovir at a standard dosage for the treatment of herpes zoster and was finally discharged, having fully returned to her normal baseline mental status with a recovered serum creatinine level of 0.68 mg/dL. We feel that awareness of this pathology remains a challenge for physicians and therefore strongly recommend the further accumulation of experiences similar to our own. Our experience underscores the pitfalls of administering valacyclovir to elderly patients who barely appear to have a favorable renal function. Several concerns regarding the therapeutic management, including blood purification strategies, that emerged in this case are also discussed.